Parameter limit and finite element analysis of unequal modulus involute gear pair - JIN ChengKe; HUANG JiaXin; ZHU ChenZe; SUN XiaoXiao; YIN Yue (Jixie qiangdu)
In order to solve the limitation of center distance adjustment and strength distribution of conventional gear, a structure with the same base pitch but different modulus was proposed to greatly improve the strength of small gears in gear transmission, especially the strength of the tooth root. But used in the engineering practice in modulus differ with tooth profile angle are smaller, the formation principle of involute gear tooth surface and the gear meshing analysis of some parameters, got this kind of gear modulus, tooth number, tooth shape parameters such as coefficient of angle, depth of constraints, and through the formula deduction coefficient of the teeth, the tooth depth and the relation between the dividing circle pressure angle limit value. Based on the modeling of engineering practice and the finite element analysis through Ansys, the gear strength designed based on the limit parameters is about 2.66 times of the standard gear, which verifies the feasibility of the theory and expands the application range of this gear pair.